2015
DOI: 10.1002/jbm.a.35578
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of common polyimides with human endothelial cells for a cardiovascular microsensor

Abstract: The cardiovasculature is an emerging niche for polyimide microdevices, yet the biocompatibility of polyimides with human endothelial cells has not been reported in the literature. In this study, we have evaluated an experimental polyimide-based pressure sensor for biological safety to determine its suitability for intravascular operation by using an in vitro model of human endothelium, following ISO 10993-5 protocols for extract tests and direct contact tests. First, SV-HCEC cells were incubated with extracts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 28 publications
(53 reference statements)
0
24
0
Order By: Relevance
“…Accordingly, in our previous report, a cuff made from polyimide had been successfully used in vascular anastomosis without the appearance of a thrombus in the reconstructed vessel [15]. Further, Starr [16] reported that polyimides including chemical sensors and blood pressure sensors are not cytotoxic to human capillary and microvascular endothelial cells. However, an in vivo study showed that polyimide-based neural implants produce a slight foreign body response, but have no effect on neural function [17].…”
Section: Discussionmentioning
confidence: 98%
“…Accordingly, in our previous report, a cuff made from polyimide had been successfully used in vascular anastomosis without the appearance of a thrombus in the reconstructed vessel [15]. Further, Starr [16] reported that polyimides including chemical sensors and blood pressure sensors are not cytotoxic to human capillary and microvascular endothelial cells. However, an in vivo study showed that polyimide-based neural implants produce a slight foreign body response, but have no effect on neural function [17].…”
Section: Discussionmentioning
confidence: 98%
“…The main applications of PI are related to the creation of biocompatible polymeric probes, in particular for the manufacture of neural and retinal implants, vascular microdevices, etc. . PMAA are widely used in various amphiphilic as well as double hydrophilic block‐copolymers for drug delivery purpose.…”
Section: Discussionmentioning
confidence: 99%
“…2 b). PI is a biocompatible polymer [22], [23] with good chemical resistance and high glass transition temperature [24], which allows for most standard photolithographic cleanroom processes. The position of the metallization between two layers of PI (Fig.…”
Section: Objectives and Backgroundmentioning
confidence: 99%